Recapturing Joaquín Chapo Guzmán in the Mexican Press: An Analysis of the Front Page of El Universal, Reforma, Excélsior, and La Jornada in 2016 (2018)
This article, whose aim is to know exactly how the headlines of Mexico's four main newspapers have reported on the recapture of Joaquín Guzmán, will show the results of an analysis of the journalistic content of these four Mexican newspapers. These are general papers, which published information on their front page regarding the recapture of the drug trafficker Joaquín 'Chapo' Guzmán. The events took place on January 8, 2016, six months after his escape from Altiplano prison in Mexico. If the escape was spectacular-being from a high-security prison and evidencing collusion of authorities and corruption of the system-the recapture was even more so. Well-known figures, such as actors Kate del Castillo and Sean Penn, were involved, together with a female politician of the Action Nacional Party, thus leading to questioning of the Mexican status quo. Coverage of the recapture was reduced, tending to minimize the impact of the criminal acts and contributing to both fictionalizing and rendering frivolous the figure of Guzmán. © 2018 The author(s).